Federated States of Micronesia: Country Report on Human Rights - Takashy, Tina (Victoria University of Wellington Law Review, 2009)
This article provides a country report on the status of human rights in the Federal States of Micronesia (FSM). FSM's legal and regulatory frameworks are a direct import of the US laws which were used during the Trust Territory of the Pacific Islands (TTPI) period. There is an inherent danger in prioritising introduced rights over traditional duties, obligations and rights – or vice versa – without subjecting these two sets of human rights paradigms to systemic sociocultural analysis. However, there are human rights issues in the FSM in any capacity. These issues originate from three major sources: poor governance and leadership capacity, weak law administrative and enforcement capacity, and outdated legal and political frameworks. The author then provides strategies to protect human rights in the Pacific including major legal and political reform, and the use of region-specific strategies (including codifying customary laws). The challenge going forward is to have in place a unified human rights model that is based on the diverse cultural, spiritual, and democratic heritage of the Pacific.